Learning Outcomes of Competency-Based Instruction Using the Concept of Community-Based Learning for Development of Learning Achievement and the Self-Management Competency of Grade 3 Students - Inchalad, Rattanaporn; Jongkonklang, Sirinat (Ratchaphruek Journal, 2024)
The objective of this study was to 1) compare the achievement of competency-based learning management using the community-based concept before and after learning and learning achievement with the 70 percent criterion 2) compare the self-management competency before and after learning, and 3) Study the learning conditions using competency-based learning management using the community-based concept. The sample was grade 3 students at Tanoenratwittayakan School, Noen Sanga District, Chaiyaphum Province. Semester 2, Academic Year 2022 was obtained by cluster random sampling. The statistics used are mean, percentage, standard deviation. t-test and Wilcoxon test. The results showed that 1) achievement was statistically significantly higher than before and after was 70 percent higher at the .05 level. 2) Self-management Competency was statistically significantly higher than before, at a level of .05, and 3) the results of a community-based competency-based learning management study. It was found that students were happy and excited because the subject they learned was related to the contextual environment in the community, which is a real-life context that students are familiar with. Interested in learning to expand thinking Plan, improve.